2008
DOI: 10.2337/dc07-2316
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supervised Progressive Resistance-Exercise Training Protocol on Insulin Sensitivity, Glycemia, Lipids, and Body Composition in Asian Indians With Type 2 Diabetes

Abstract: OBJECTIVE -To evaluate the effect of supervised progressive resistance-exercise training (PRT) protocol on insulin sensitivity, glycemia (blood glucose and A1C levels), lipids, and body composition in Asian Indians with type 2 diabetes.RESEARCH DESIGN AND METHODS -Thirty patients with type 2 diabetes underwent 12 weeks of PRT of six muscle groups (two sets, 10 repetitions each). The subjects were evaluated with detailed anthropometry and with measurements of the disappearance of glucose per unit time (K) durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
111
1
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(127 citation statements)
references
References 22 publications
7
111
1
8
Order By: Relevance
“…Our findings on the effect of exercise on blood sugar were similar with previous findings. 5,21,[26][27][28][29][30] Nevertheless, results of a study by Karstoft et al differed from our findings. 31 These differences may be due to the participant's characteristics.…”
Section: Discussioncontrasting
confidence: 57%
“…Our findings on the effect of exercise on blood sugar were similar with previous findings. 5,21,[26][27][28][29][30] Nevertheless, results of a study by Karstoft et al differed from our findings. 31 These differences may be due to the participant's characteristics.…”
Section: Discussioncontrasting
confidence: 57%
“…9,10 Several reviews on the effects of diet and exercise on the incidence of CHD and type 2 diabetes have emphasised their importance in the primary and secondary prevention of disease. [11][12][13] With South Asian populations identified as less physically active than the general population, 14,15 alongside growing concern about child and adult obesity, 16 culturally appropriate and effective interventions in this high-risk group are urgently needed. 17 However, little is known about relevant experience of such interventions with South Asian populations.…”
Section: Introductionmentioning
confidence: 99%
“…A similar study conducted on Asian Indians with Type 2 Diabetes showed that a moderate-intensity PRT for 3 months resulted in a significant improvement in insulin sensitivity, glycemia, lipids, and truncal and peripheral SCAT in patients with Type 2 DM, but no significant changes were noticed in BMI or levels of total body fat, truncal fat, and lean body mass [15]. However, in our study there were significant improvements in muscle and bone density as well as reductions in body fat percentage and visceral fat which were positively related to reductions in FBG total cholesterol level.…”
Section: Discussionmentioning
confidence: 97%